Gynostemma pentaphyllum for dyslipidemia: A systematic review of randomized controlled trials - Dai, Ning; Zhao, Fang-fang; Fang, Min; Pu, Feng-lan; Kong, Ling-yao; Liu, Jian-ping (Frontiers in Pharmacology, 2022)
Objective: To evaluate the lipid-lowering effect and safety of Gynostemma pentaphyllum (GP) used alone or as an adjunctive therapy for dyslipidemia. Methods: Eight databases and three clinical trial registries were searched until January 2022. Randomized controlled trials (RCTs) assessing effectiveness of GP for dyslipidemia were included. Trial quality was assessed by Cochrane Risk of Bias Tool 2.0. Data were analyzed by RevMan 5.4 with effects estimated as risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CI). Results: Twenty-two RCTs involving 2,407 dyslipidemia participants were included. In terms of risk of bias, 14 RCTs had some concerns, seven RCTs were high, and one trial was low. GP was comparable to n-3 fatty acids (RR 0.89, 95% CI 0.62 to 1.28) and red yeast rice (RR 0.33, 95% CI 0.1 to 1.12 on normalization of serum lipids. GP plus n-3 fatty acid was superior in normalization of triglycerides (TG) and total cholesterol (TC) than n-3 fatty acids (RR 1.34, 95% CI 1.01 to 1.77). GP was similar to lipid-lowering agents (statins, fibrates, and n-3 fatty acids) in regulating TG, TC, and high-density lipoprotein cholesterol (HDL-C). GP plus lipid-lowering agents was superior than lipid-lowering agents in TG (MD -0.65 mmol/L, 95% CI -1.03 to -0.28), LDL-C (MD -0.57 mmol/L, 95% CI -1.07 to -0.08), and HDL-C (MD 0.15 mmol/L, 95% CI 0.11 to 0.20). GP was inferior to red yeast rice in TC (MD 0.64 mmol/L, 95% CI 0.15 to 1.13), TG (MD 0.43 mmol/L, 95% CI 0.15 to 0.71), and HDL-C (MD -0.25 mmol/L, 95% CI -0.47 to -0.04). GP had fewer adverse events than lipid-lowering drugs. Conclusion: Very low certainty evidence showed GP’s effects on TC, TG, HDL-C were comparable to that of lipid-lowering agents. Low certainty evidence showed that red yeast rice was superior than GP in TC, TG, and HDL-C. From low to moderate certainty evidence showed that the effects of GP plus lipid-lowering agents were superior than that of lipid-lowering agents on TG, LDL-C, and HDL-C. Its use for more than eight weeks appears safe.